2003
DOI: 10.1128/iai.71.9.4996-5004.2003
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis Decreases Central Nervous System Inflammation and Alters the Progression of Experimental Autoimmune Encephalomyelitis

Abstract: A preestablished infection with the parasitic helminth, Schistosoma mansoni, significantly reduced the incidence and delayed the onset of experimental autoimmune encephalomyelitis (EAE) in C57BL/6J mice immunized with myelin oligodendrocyte glycoprotein (MOG) 35-55 peptide. The altered disease progression was not solely due to the induction of a strong Th2 response, since intraperitoneal injection of schistosome eggs did not affect disease development. MOG-specific gamma interferon (IFN-␥), nitric oxide, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
198
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(206 citation statements)
references
References 45 publications
6
198
0
2
Order By: Relevance
“…mansoni infection seems to be protective against asthma (Medeiros et al 2003, Araujo et al 2004. Using mice models of S. mansoni infection it has been demonstrated that this parasite also protects against the development of auto-immune disease such as diabetes, experimental auto-immune encephalopathy, and Crohn's disease (Cooke et al 1999, Elliott et al 2003, La Flamme et al 2003, Sewell et al 2003, Zaccone et al 2003. Some of these studies suggest that IL-10 is a key cytokine involved in the modulation of the inflammatory immune response observed in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…mansoni infection seems to be protective against asthma (Medeiros et al 2003, Araujo et al 2004. Using mice models of S. mansoni infection it has been demonstrated that this parasite also protects against the development of auto-immune disease such as diabetes, experimental auto-immune encephalopathy, and Crohn's disease (Cooke et al 1999, Elliott et al 2003, La Flamme et al 2003, Sewell et al 2003, Zaccone et al 2003. Some of these studies suggest that IL-10 is a key cytokine involved in the modulation of the inflammatory immune response observed in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…mansoni infection also decreased tissue damage and clinical manifestation of others Th1-mediated autoimmune diseases such as multiple sclerosis and Crohn's disease. In a mice model to study experimental autoimmune encephalite (EAE), a multiple sclerosis like disease, it was demonstrated that infection with S. mansoni delays the onset of the disease and prevents inflammation in the central nervous system (La Flamme et al 2003, Sewell et al 2003). Attenuation of the clinical course of EAE was followed by a reduction in the synthesis of pro-inflammatory mediators, such as IFN-γ, TNF-α and NO, by spleen and central nervous cells in vitro, while the levels of IL-4 and IL-5 in plasma were, as predicted, higher in the parasite-infected group (La Flamme et al 2003).…”
Section: The Role Of Parasite Infection On the Suscep-tibility Of Autmentioning
confidence: 99%
“…In a mice model to study experimental autoimmune encephalite (EAE), a multiple sclerosis like disease, it was demonstrated that infection with S. mansoni delays the onset of the disease and prevents inflammation in the central nervous system (La Flamme et al 2003, Sewell et al 2003). Attenuation of the clinical course of EAE was followed by a reduction in the synthesis of pro-inflammatory mediators, such as IFN-γ, TNF-α and NO, by spleen and central nervous cells in vitro, while the levels of IL-4 and IL-5 in plasma were, as predicted, higher in the parasite-infected group (La Flamme et al 2003). Although the production of IL-10 did not differ between mice that were infected or not with S. mansoni in this study, in the EAE S. mansoni ova immunization lead to production of IL-10 and TGF-β, in addition to IL-4, by spleen cells in vitro, and decreased IFN-γ synthesis (Sewell et al 2003).…”
Section: The Role Of Parasite Infection On the Suscep-tibility Of Autmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study does not distinguish between the contribution of macrophages, microglia and neutrophils, but because lymphocytes and macrophages were the predominant cells infiltrating the CNS and from our previous results on the function of alternatively activated macrophages, 27,36 we suspect macrophages to be the principal effector cells. Furthermore, interactions between infiltrating macrophages and T cells are believed to be responsible for microglial activation, and it has been demonstrated that microglia are not appropriately activated in the absence of blood-borne macrophages.…”
Section: Discussionmentioning
confidence: 77%